2015
DOI: 10.1109/jsen.2015.2416651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Improving the Depth Accuracy of Kinect for Windows v2

Abstract: Microsoft Kinect sensor has been widely used in many applications since the launch of its first version. Recently, Microsoft released a new version of Kinect sensor with improved hardware. However, the accuracy assessment of the sensor remains to be answered. In this paper, we measure the depth accuracy of the newly released Kinect v2 depth sensor, and obtain a cone model to illustrate its accuracy distribution. We then evaluate the variance of the captured depth values by depth entropy. In addition, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(181 citation statements)
references
References 21 publications
(16 reference statements)
2
174
0
5
Order By: Relevance
“…When a person stands in front of the sensor, it captures color image and the depth image of the person using the RGB, IR and depth sensors. Then the background noise and moving objects are identified using image processing techniques in the sensor middleware [11]. The depth information of the user's body was identified according to the user position.…”
Section: Methodsmentioning
confidence: 99%
“…When a person stands in front of the sensor, it captures color image and the depth image of the person using the RGB, IR and depth sensors. Then the background noise and moving objects are identified using image processing techniques in the sensor middleware [11]. The depth information of the user's body was identified according to the user position.…”
Section: Methodsmentioning
confidence: 99%
“…However, possible sensor limitations are related to inaccuracies regarding the coordinates of the captured 3D data, especially for short and long range distances (Yang et al, 2015). To address these difficulties, in this paper, we introduce a methodology which exploits the spatiotemporal coherency of a human movement in order to compensate the depth inaccuracies of the Kinect sensor.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In the article of Yang [16], an MS Kinect v2 structure is proposed to improve the accuracy of the sensors and the depth of capture of objects that are placed more than four meters apart. It has been concluded that an object covered with light-absorbing materials, may cause less reflected IR light back to the MS Kinect and therefore erroneous depth data.…”
Section: Accuracy Estimation Methodologies For 3d Vision Sensorsmentioning
confidence: 99%